Web-Based Tourism Geographic Information System in Banggai Laut Regency - Suhada, Sitti; Dai, Roviana H; Imudi, La (UNIVERSITAS RAHARJA, 2023)
Banggai Laut Regency has abundant natural resources, both in the form of marine resources and from various produce. abundant resources in Banggai Laut Regency, making this district one of the places that have tourist destinations. Some of the tourist attractions that can be found in Banggai Laut Regency are very diverse including natural tourism, cultural tourism and tourist villages. Limited information about the types of tourism, the distribution of tourist locations, tourist maps are the causes of the undeveloped tourist attractions in the Banggai Laut Regency area. This research raises the issue of how to create a web-based tourism geographic information system in Banggai Laut Regency. The purpose of this study is to create a web-based tourism geographic information system. The method used in this study is the prototyping system development method. This research produces a web-based tourism geographic information system in Banggai Laut Regency. With the existence of a geographic information system, it can help tourists to be able to find out how the description of tourist attractions, tourist maps, and information about tourist attractions to be visited, so that tourists get detailed information in traveling and visiting tourist destinations and help the local government, especially the Tourism Office in promoting tourist attractions in Banggai Laut Regency.